Seeded Free-Electron Lasers and Free-Electron Laser Applications. Issue 3 (3rd May 2016) - Parmigiani, Fulvio; Ratner, Daniel
Abstract : Several decades after the groundbreaking discovery of X-rays in 1895 by Wilhelm Conrad Roentgen, it became quite evident that the possibility of building X-ray sources with controlled photon beam parameters was a revolutionary step to address some of the important challenges facing humanity. The awareness that these sources could dramatically improve mankind's scientific knowledge and technological ability was at the base of significant investments and scientific programs worldwide that brought X-ray sources into the present "golden age."